2001
DOI: 10.4049/jimmunol.167.10.5731
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance, Mixed Chimerism, and Chronic Transplant Arteriopathy

Abstract: Much evidence supports the conclusion that immunological responses to donor-specific incompatibilities are a major factor in producing “chronic” transplant rejection, including the arteriopathy (atherosclerosis) commonly present. Our experiments explored the effects of altered immunological responsiveness to these Ags on the formation of arteriopathy in transplanted mouse hearts. Specific immunological nonreactivity, or tolerance, was induced either by neonatal administration of allogeneic spleen cells (from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 53 publications
6
62
0
Order By: Relevance
“…One could surmise that researchers in the field have a pre-determined bias (full tolerance is the preferred outcome clinically), as evidenced by the numerous studies that chose to use clinically irrelevant MHC-congenic donors (minor antigen-matched) that are likely to give a false impression of full tolerance (skin acceptance) [16,[38][39][40][41][42][43][44], including in protocols very similar to our own [45]. No explanation is given in such studies for the unusual choice of donor/recipient combination.…”
Section: Discussionmentioning
confidence: 99%
“…One could surmise that researchers in the field have a pre-determined bias (full tolerance is the preferred outcome clinically), as evidenced by the numerous studies that chose to use clinically irrelevant MHC-congenic donors (minor antigen-matched) that are likely to give a false impression of full tolerance (skin acceptance) [16,[38][39][40][41][42][43][44], including in protocols very similar to our own [45]. No explanation is given in such studies for the unusual choice of donor/recipient combination.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they play an important role in the rejection of xenograft cells. 41,42 In our xenogeneic cell transplantation model, the infiltrated macrophages (CD68 þ cells) were observed only at the border region of the outer annulus and the endplate in the early stages following transplantation. The increased CD68 þ cells on days 1 and 10 suggest that macrophages are involved with the graft response, which is not normally associated with inflammatory cells.…”
mentioning
confidence: 99%
“…We previously demonstrated that cardiac allografts to mixed chimeric mice developed cardiac allograft vasculopathy (CAV), even though they were tolerant of donor antigens confirmed by donor strain skin graft survival (1). These findings suggested that innate immune responses might be involved in the process.…”
Section: Introductionmentioning
confidence: 99%
“….A/B6 mixed chimeric mice were created by receiving injections of anti-CD4/CD8 mAbs and CD40L mAb, 3Gy WBI, and bone marrow cells from B10.A (H-2 k ) mice given to C57BL/ 6 (B6; H-2 b ) mice as previously described (1,8,9). At 8 weeks after the induction of mixed chimerism, B10.A skin grafts were placed onto B6/B10.A chimeric recipients to confirm that they were tolerant of donor antigens in vivo.…”
Section: B10mentioning
confidence: 99%